Does inflation targeting lower inflation and spur growth? - Ayres, Kelly (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2014)
Over the last few decades several countries have turned to inflation targeting as a policy choice for instilling stability into their economies. Prior studies have shown that inflation targeting has reduced inflation in those countries without significantly impacting GDP. This study seeks to improve upon these results by identifying the impact of timing on the policy decision as well as its impact as related to specific regions of the world. The focus is on developing countries across six regions. We find significant regional variation in developing countries in our sample in terms of the direction of changes in inflation following a switch to the inflation targeting policy. Moreover, although the impact of inflation targeting on real GDP is minimal overall, there is a statistically significant increase in real GDP among developing countries in certain regions only, namely, Europe, Latin America, and the Middle East.